2020
DOI: 10.3390/v12060639
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Polyunsaturated Fatty Acids Impede the TCR Mobility and the TCR–pMHC Interaction of Anti-Viral CD8+ T Cells

Abstract: The immune-suppressive effects of omega-3 (n-3) polyunsaturated fatty acids (PUFAs) on T cells have been observed via multiple in vitro and in vivo models. However, the precise mechanism that causes these effects is still undefined. In this study, we investigated whether n-3 PUFAs regulated T cell receptor (TCR) and peptide-major histocompatibility complex (pMHC) interactions. The expansion of anti-viral CD8+ T cells that endogenously synthesize n-3 PUFAs (FAT-1) dramatically decreased upon lymphocytic choriom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…Additionally, CD3-labeled T cells were present only in the dermal compartment of PS +T+ALA , confirming that the addition of ALA to the culture medium decreased the migration of T cells towards the dermo-epidermal junction. A recent study revealed that the percentage of CD45+ cells among CD8+ T cells was decreased in FAT-1 mice, which are capable of producing n-3 PUFAs independently [53]. The decreased expression of ICAM-1 in PS +T+ALA also confirms that ALA minimizes the ability of T cells to bind to keratinocytes in the psoriatic substitutes.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, CD3-labeled T cells were present only in the dermal compartment of PS +T+ALA , confirming that the addition of ALA to the culture medium decreased the migration of T cells towards the dermo-epidermal junction. A recent study revealed that the percentage of CD45+ cells among CD8+ T cells was decreased in FAT-1 mice, which are capable of producing n-3 PUFAs independently [53]. The decreased expression of ICAM-1 in PS +T+ALA also confirms that ALA minimizes the ability of T cells to bind to keratinocytes in the psoriatic substitutes.…”
Section: Discussionmentioning
confidence: 80%
“…This could be a potential pathogenetic mechanism for the loss of T lymphocytes which has been observed during SRV infection. Interestingly, Lim et al demonstrated that omega-3 ( n -3) polyunsaturated fatty acids (PUFAs) interfere with MHC-TCR interactions in CD8 + T cells [ 6 ]. In this study, highly inclined and laminated optical sheet microscopic analysis was used to uncover how TCR motility was reduced on the anti-viral CD8 + T cells that endogenously synthesize n -3 PUFAs.…”
mentioning
confidence: 99%